Microfluidic chip using foil‐assisted CO2 laser ablation for suspended particle separation. (1st October 2015) - Chung, Chen‐Kuei; Long, H.P.; Lai, C.C.
Abstract : Separation is one of the important pretreatment processes during detection in lab‐on‐a‐chip. In this reported work, polydimethylsiloxane (PDMS) on a glass microchip with a combination of the spiral channel and backward facing step structure was designed to optimise the separation of suspended particles without any extra active powers of the electric or magnetic field. The spiral microfluidic chip was fabricated first by the foil‐assisted CO2 laser ablated polymethylmethacrylate (PMMA) master mould, followed by repetitive PDMS moulding and then bonded to a glass substrate. The CO2 laser ablation of PMMA in air normally generated poor surface quality comprising bulges and scorches. The metal‐foil‐assisted laser ablation can effectively improve the above defects with conducting cover protection. The average height of the bulges was reduced from 5.0 to 1.5 μm and the channel width was reduced from 230 to 120 μm. The finished separation chips were operated at various syringe‐controlled flow rates of 5–20 µL/min to test the performance. A high separation efficiency of about 99% could be achieved within a certain flow range of less than 15 µL/min under the simple structure with low‐cost and time‐saving.